A child with distal (type 1) renal tubular acidosis presenting with progressive gross motor developmental regression and acute paralysis. (December 2017) - Ranawaka, Randula; Dayasiri, Kavinda; Gamage, Manoji
Abstract Background Distal (Type 1) renal tubular acidosis (dRTA) is characterized by inability to secrete hydrogen irons from the distal tubule. The aetiology of dRTA is diverse and can be either inherited or acquired. Common clinical presentations of dRTA in the paediatric age group include polyuria, nocturia, failure to thrive, constipation, abnormal breathing and nephrolithiasis. Though persistent hypokalemia is frequently seen in dRTA, hypokalemic muscular paralysis is uncommon and rarely described in children. Case presentation Three and a half years old girl was referred for evaluation of progressive loss of gross motor milestones over 6 months and acute episode of paralysis. Her other developmental domains were age appropriate. Notably, there was no history of polyuria, polydipsia, nocturia and abnormal breathing. Physical examination revealed proximal myopathy (waddling gait and positive Gower's sign), diminished lower limb reflexes and muscle tone. Her serum potassium was low (2.1 meq/l) and she was subsequently investigated for hypokalemic paralysis. Diagnosis of distal renal tubular acidosis was made, based on hypokalemic hyperchloremic metabolic acidosis with normal anion gap, high urine pH, borderline hypercalciuria, medullary nephrocalcinosis and exclusion of other differential diagnosis. The child showed complete symptomatic recovery upon commencement of standard treatment for distal renal tubular acidosis. Conclusions This case report highlights the importance of considering hypokalemia and renal tubular acidosis in the differential diagnosis of acute flaccid paralysis and proximal myopathy. Early diagnosis will prevent costly investigations and enable rapid clinical recovery in the affected child.